Upaya Keluarga Dalam Meningkatkan Kualitas Hidup Pasien Hemodialisa - Nabila, Witri Setiawati; Juwita, Lisavina (Universitas Fort De Kock Bukittinggi, 2020)
Background: Chronic kidney failure or end-stage kidney disease is impaired kidney function. It is progressive and irreversible. One way to maintain survival with hemodialysis, dependence on hemodialysis will reduce the quality of life of patients. The purpose of this research was to describe, analyze and interpret family efforts to improve the quality of life of patients with chronic renal failure undergoing hemodialysis therapy in Dr. Achmad Mochtar Bukittinggi. Method: The type of this research was qualitative with phenomenological approach. It was conducted on July 2019. Then, by using purposive sampling technique, 6 people had been chosen as the samples. The data were collected through in-depth interviews and it was by analyzed colaizzi method. Results: The results of the research obtained that about the family efforts in improving the quality of life of patients described into 4 themes: 1) assisting in meeting physiological needs, 2) providing psychological support, 3) assisting in social activities, 4) assisting in solving environmental problems. In short, family efforts both in improving the quality of life of patients were viewed from physical health, psychological health, social and environmental relations. Conclusion: : Then, it is expected that families to make maximum efforts to improve the quality of life of patients.Keywords: Quality of Life, Hemodialysis, Family Effort